Automatic billing counterfeit detection for SGD money - Arun Ramchandani. (2010)
Production of counterfeit notes is a crime carried out by professional criminals who acquire skills from current technology to produce flawless notes 100% accurate to the genuine bills. Cases have been highlighted as retailers and consumers have been duped due to counterfeit note scams. One of the biggest reasons why most counterfeit notes have been passed off as genuine ones is simply due to the cashier‘s failure to carry out basic checks especially during busy periods of large sales.